2019
DOI: 10.18502/ijph.v48i1.778
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Air Pollution and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Background: During the past 20 years, the prevalence of gestational diabetes mellitus (GDM) has increased by ∼10%-100% in several race/ethnicity groups. There is an association between ambient air pollution (AAP) and GDM. This study aimed to summarize the evidence about the association between AAP and GDM. Methods: PubMed, Embase, Scopus, Web of Science and Cochrane Library were searched from inception till Oct 2017. Studies about the association between ambient air pollutants levels and GDM were included. Poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…Genetic difference [39], different lifestyle (e.g., physical activity) [40] and diet [41] (four days) was associated with higher FBG concentration as well as IFG occurrence [45]. A systematic review and meta-analysis by Elshahidi et al 2019 found that higher PM 2.5 and PM 10 exposures were associated with GDM development [46]. These reports are in line with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…Genetic difference [39], different lifestyle (e.g., physical activity) [40] and diet [41] (four days) was associated with higher FBG concentration as well as IFG occurrence [45]. A systematic review and meta-analysis by Elshahidi et al 2019 found that higher PM 2.5 and PM 10 exposures were associated with GDM development [46]. These reports are in line with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…A part of this study (i.e., signi cant positive association between PM 2.5 exposures and FBG concentration) is in line with our ndings; while, the associations of 1h and 2-h glucose were inconsistent with our ndings. Another study by Fleisch [29]. These reports are in line with our ndings.…”
Section: Available Evidencesupporting
confidence: 92%
“…A study by Chen et al 2016, reported that short-term exposure to PM 10 (four days) was associated with higher FBG concentration as well as IFG occurrence [45]. A systematic review and meta-analysis by Elshahidi et al 2019 found that higher PM 2.5 and PM 10 exposures were associated with GDM development [46]. These reports are in line with our ndings.…”
Section: Available Evidencesupporting
confidence: 88%